Tandetron - pomembno orodje za študij materialov - Žitnik, Matjaž (Kovine zlitine tehnologije, 1999)
The new ion accelerator in operation at Microanalitical Center (MIC) of J. Stefan Institute in Ljubljana is presented. Several Ion Beam Analysis (IBA) methods are intoduced and some of the results obtained on the new location are reported.
Keywords: ionski pospeševalniki; spektroskopija